PENGEMBANGAN BAHAN AJAR MENULIS ESAI BERMUATAN BUDAYA NUSANTARA DALAM BENTUK CD INTERAKTIF : Studi R&D di JurusanPendidikanBahasadanSastra Indonesia FPBS UPI TahunAkademik 2012/2013 - Farihah, Siti (2014)
Keterampilanmenulisesaidiperlukanmahasiswauntukmengasahkekritisantehadapberbagaipermasalahantermasukbudaya yang ada di sekitarmereka, terlebihlagibudayabangsa Indonesia sebagaicerminjatidiribangsajustrudiabaikandanbeberapabudayadiakuiolehbangsalain, itumenunjukkanbahwakepeduliangenerasimudasangatkurang, padahalnantinyagenerasiinilah yang akanmelestarikanbudaya yang telahada. Tujuandaripenelitianiniyaitumembuatbahan ajar menulisesaidalambentuk CD interaktif.Penelitianinimenggunakanmetodepenelitianresearch and development (R&D).Instrumenpenelitianmeliputilembarwawancara, angket, lembarobservasi, tes,danlembarujivalidasi.Analisisprofilmenggunakanlembarobservasi, angketdanwawancara, sementaraujicobaterbatasmenggunakanlembarobservasidantesdanvalidasiprototipebahan ajarmenggunakanlembarujivalidasi, danujicobapemakaianmenggunakanangkettanggapandantes.Data yang terkumpuldianalisisdenganmetodedeskriptifkualitatifdankuantitatif. SampelpenelitianiniadalahmahasiswaJurusanPendidikanBahasadanSastra Indonesia semester IIIdan semester I. Setelahpenelitiandilakukan, diperolehhasilsebagaiberikut: (1) profilterkaitpembelajaranmenulisesai di JurusanPendidikanBahasadanSastra Indonesia yaitumahasiswakesulitanmenemukan ide danmengembangkannya, mengawalidanmenyusunkalimatefektif, merangkaigagasan yang ada;(2) proses pembelajaranmenulisesaicenderungmenggunakanbuku ajar, dosenbelummengembangkanbahansecara optimal, fungsibahan ajar untukpedomanmahasiswadalampembelajaran;(3) Pengembanganbahan ajar menulisesaimeliputi a) bentukfisikyaitukotakpembungkusCD, desainisiyaitu visual, audio, dantulisan; b) muatanisibahanajar; c) karakteristikbahan ajar; (4) produk akhir pengembangan berupa CD interaktif pembelajaran menulis esai telah divalidasi oleh dosen ahli bahan ajar menulis, ahli budaya, ahli teknologi pendidikan, dosen mata kuliah menulis, teman sejawat serta hasil perbaikan ujicoba terbatas dan ujicoba pemakaian kepada mahasiswa. Tanggapan mengenai penggunaan CD menurut dosen dan mahasiswa menarik dan mudah digunakan, sedangkan menurut ahli CD interaktif layak digunakan untuk pembelajaran menulis esai bermuatan budaya. The skill of essay writing is required by students to sharpen their critical thinking towards some issues including culture around them, especially the culture of Indonesia as the reflection of national identity which is ignored and recognized by other nations. It shows that the younger generation is less concern to that issue, whereas this is the generation that eventually will preserve the existing culture in the future. The purpose of this study is to make teaching materials for essay writing in form of interactive CD. This study uses Research and Development (R&D) research method. Research instruments include questionnaire, observation sheet, test, and validation test sheet. The analysis of profile uses observation sheets, questionnaires and interviews, while limited trials uses observation sheets and test, the validation of teaching materials prototype uses validation test sheet, and the test of the application uses responses questionnaire and test. The data are analyzed with descriptive qualitative and quantitative methods. The sample is the third and first semester students of Indonesian Language and Literature Education Department. Once the research is done, results obtained are: (1) profile related to essay writing learning in Indonesian Language and Literature Education Department is that students have trouble to find ideas, initiate and organize effective sentences, and string the existing ideas; (2) the process of essay writing learning tends to use textbooks, the lecturers have not developed teaching materials optimally to guide students in learning; (3) the development of teaching materials of essay writing include a) physical form i.e. CD packaging boxes, content design i.e. visual, audio, and text; b) the contents of teaching materials; c) the characteristics of teaching materials; (4) the final product of the development in the form of an interactive CD has been validated by expert lecturers of teaching materials in writing, cultural expert, educational technology expert, lecturer in writing, peers and the results of repair limited test and trial use. Responses regarding the use of CD from faculty and students are that the CD is attractive and easy to be used, while according to experts, the interactive CD is suitable to be used for the learning of essay writing with cultural content.